Alflutop clinical efficacy assessment in osteoarthritis (two-years study) - V. N. Chodyrev; N I Znaisheva; G M Lobanova; L M Ridnyak (Научно-практическая ревматология, 2003)
Objective. To assess alflutop clinical efficacy and safety during long-term course treatment of knee osteoarthritis. Methods. 51 pts with definite knee osteoarthritis of I-III stage according to Kellgren-Lawrence classification were included in an open controlled study. 20 pts received 6 intra-articular injections of alflutop 2 ml with subsequent intramuscular treatment during 3 months. Such courses were repeated 6 months apart for 2 years. 31 pts of control group received nonsteroidal anti-inflammatory drugs (NSAID) only. Pain on visual analog scale, Leken functional score, changes of NSAID treatment and radiological picture were used for assessment of efficacy. Clinical examination was performed before and after every treatment course and 3 months after the last course. Results. Every alflutop treatment course provided significant stepwise decrease of pain with improvement of mobility, reduction of NSAID requirement and absence of osteoarthritis radiological progression. Doctor and pts clinical efficacy and safety assessment coincided. Conclusion. Alflutop is an effective drug for knee osteoarthritis treatment. It has anti-inflammatory and probably chondroprotective activity with good safety.